Analysis of outcome indicators in clinical trials related to feeding intolerance in ICU patients receiving enteral nutrition feeding - He, Chaokai; Li, Xiaorong; Li, Fan; Xia, Ying; Yu, Kunrong (Frontiers in Nutrition, 2025)
PurposeThe aim of this study was to analyze the outcome indicators of clinical trials related to feeding intolerance in patients receiving enteral nutrition feeding in ICUs published in the past 10 years, and to provide data support for the construction of a core outcome set for clinical trials on feeding intolerance in ICU patients.MethodsThe databases of Cochrane Library, Pubmed, Embase, SinoMed, Wanfang Data and China Knowledge Network (CNKI) were searched using a combination of free and subject terms. The time limit was from January 2013 to September 2023. Literature screening and data extraction were carried out independently by two researchers strictly according to the inclusion and exclusion criteria, and in case of disagreement, the decision was discussed by a third party.ResultsA total of 52 papers reporting 138 different outcome indicators were included in this study. Indicators were categorized into 8 domains based on their functional characteristics. In descending order of frequency of reporting, they were symptoms and signs (82.7%), physical and chemical tests (75%), indicators related to nutritional support (63.5%), safety events (59.6%), long-term prognosis (34.6%), economic assessment (21.2%), functional status (5.8%), and satisfaction (3.8%). The top 10 most frequently reported outcome indicators were diarrhea, vomiting, bloating, gastric remnants, reflux, aspiration, gastric retention, mortality, albumin and constipation. The main problems with the indicators included a lack of systematicity, clinical utility, and standardization of reporting, as well as inconsistency in the time point of measurement and misuse of the indicators.ConclusionThe lack of core outcome sets had led to significant variability and non-standardization in the outcome indicators reported by Enteral Feeding Intolerance clinical studies. Enteral Feeding Intolerance is an important factor affecting the prognosis of critically ill patients, and the outcome indicators of its clinical studies need to be standardized. It is recommended that a core outcome set for Enteral Feeding Intolerance be constructed to standardize the reporting of outcome indicators in future studies, reduce inter-study heterogeneity, and improve the utility of study results and the quality of clinical decision-making.